Comparison of Factors Related to Mathematics Achievement of Mathayomsuksa 3 Students Classified According to School Size - Prutthisan, Chanmanee; Tippayakulpairoj, Darunee; Srihaset, Kamontip (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: Mathematics learning management at the junior high school level focuses on developing students in both knowledge and mathematical process skills. However, from the results of both national and international evaluations, it was found that mathematics learning management has not been successful. In addition, teaching and learning arrangements vary according to the size of the school. This research article aims to (1) study the levels of factors that are related to mathematics achievement of Mathayom 3 students and (2) compare the factors that are related to achievement. Mathematics learning of Mathayom 3 students are classified by school size. Methodology: The sample used in the research was 543 Mathayom 3 students under the Udon Thani Secondary Educational Service Area Office using multi-stage random sampling. The research instrument was a questionnaire. Data was analyzed using one-way multiple analysis of variance. Results: (1) Basic knowledge in mathematics had an average of 68.04, for the quality of teachers’ teaching had an average score of 3.96, attitude towards mathematics had an average of 3.85, learning environment had an average of 3.80, the relationship between students and friends had an average of 3.78, parents’ academic support had an average of 3.72, perceived ability to study mathematics had an average of 3.58, and mathematics study behavior had an average of 3.55, respectively. (2) Attitudes towards mathematics in the learning environment and basic knowledge of mathematics differed between school sizes, at the significance level of .05. As for the quality of teachers’ teaching perception of learning ability in mathematics, relationships between students and friends, parents’ academic support and mathematics study behavior, no differences were found between school sizes. Conclusion: Research results indicate that the first set of results outlines the average scores for various components related to mathematics education. The second set of results indicates significant differences in attitudes towards mathematics and basic knowledge among students from different school sizes, while no significant distinctions were found in perceptions of teacher quality, learning ability, relationships, parental support, and study behavior based on school size. These findings suggest that certain aspects of mathematics education may be influenced by school size, while others remain consistent across different school settings.